Pilot randomised controlled trial of face-down posturing following phacovitrectomy for macular hole - Yorston, D (Nature Publishing Group, 2012)
BACKGROUND: To gather information on the effect of postoperative face-down posturing following combined phacoemulsification and vitrectomy for macular hole surgery in order to assist in the design of a larger definitive study. METHODS: Thirty phakic patients with stage II–IV full-thickness macular hole had combined phacoemulsification and pars plana vitrectomy with internal limiting membrane peel and 14% perfluoropropane (C(3)F(8)) gas. At the conclusion of surgery, patients were randomised either to face-down posture or to no posture, for 10 days. The primary outcome was macular hole closure. RESULTS: The macular hole was successfully closed in 93.8% of the face-down posture group and in all of the no-posture group. Mean visual improvement was 0.63 (SD=0.21) logMAR units in the face-down group and 0.53 (SD=0.22) in the no posture patients. CONCLUSION: Following combined phacoemulsification and vitrectomy, postoperative face-down posturing appears to make little difference to the final anatomical or visual outcome. If we assume a success rate of 95% in the posturing arm, and that there is no difference between posturing and non-posturing, then 798 patients would be required to be 90% sure that the 95% confidence interval will exclude a difference of more than 5%.